The Influence of Occupational Health and Safety (OHS) Programs, Work Environment, and Workload on Employee Performance at PT. PLN (Persero) UIW Sulutenggo UP3 Gorontalo ULP Telaga - Komang Budiarta; Lisda L. Asi; Endi Rahman (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to (1) determine the influence of occupational health and safety on employee performance at PT PLN (Persero) Sulutenggo Regional Main Unit (UIW) UP3 Gorontalo, ULP Telaga; (2) determine the influence of the work environment on employee performance; and (3) determine the influence of workload on employee performance. The study sample consisted of 112 respondents, and the analytical tool used was multiple linear regression. Furthermore, the study employed a descriptive quantitative method, collecting data both online through Google Forms and offline via questionnaires. The findings indicate that (1) partially, Occupational Health and Safety (OHS) program significantly influences employee performance, with a significance value of 0,000 < 0,05 and T count value > T table (5,011 > 0,676); (2) partially, work environment has a significant influence on employee performance, with a significance value of 0,000 < 0,05 and T count value > T table (3,615 > 0,676); (3) partially, workload has a significant influence on employee performance, with a significance value of 0,000 < 0,05 and T count value > T table (5,297 > 0,676); and (4) simultaneously, occupational health and safety, work environment, and workload have a positive and significant influence on employee performance, with a significance value of 0,000 < 0,05 and F count value > F table (16,536 > 2,69). The determination coefficient (R) is 0,661, indicating a moderate correlation, whereas the R-square value is 0,437, which indicates that 43,7% of employee performance is influenced by occupational health and safety programs, work environment, and workload, whereas the remaining 57,3% is influenced by other variables not examined in this study, such as compensation, motivation, leadership, training, and other factors that can be explored in future research.